Entrepreneurship Education Influencing Technopreneurship for Student Innovation in the Industrial Revolution Era 4.0 - Yulina Ismiyanti; Juhadi Juhadi; Melly Agustina Permatasari; Deka Setiawan; Rudi Salam (Universitas Negeri Semarang, 2021)
Being in the era of globalization 4.0, all aspects of life have shifted to adapt to these developments. Including the world of education at the university, which is the spearhead of change. Entrepreneurship education, which is a university course that used to be taught conventionally, is now starting to include technology in entrepreneurship which is packaged with technopreneurship. This study aims to analyze entrepreneurship education influencing the ability of technopreneurship on student innovation in the industrial revolution 4.0 era. The subjects of this research are UNISSULA students. Sampling refers to Yount's table obtained by 252 UNISSULA students. The sample is grouped into two. Group I has received 162 students of entrepreneurship and technopreneurship learning materials. Group II has not received entrepreneurship and technopreneurship learning materials, totaling 90 students. Data collection was obtained through a questionnaire. Data analysis using Structural Equation Model (SEM). Based on the research, entrepreneurship education has a role in influencing students' technopreneurship abilities on student innovation in the era of the industrial revolution 4.0.